Situational xylophagia from chronic anemia: case report - Credo, Jonathan; Mubarik, Sumra; Scher, Lorin M. (Frontiers in Psychiatry, 2025)
BackgroundXylophagia is a rare subtype of pica involving consumption of paper or wood products. It is unknown why an individual may choose non-food items for consumption; however, pica has higher co-occurrence in those with schizophrenia, intellectual disability, or mineral deficiency.Case presentationWe present a case of a patient with severe abdominal pain and a small bowel obstruction due to a paper bezoar (xylobezoar). Evaluation led to a diagnosis of xylophagia in the context of chronic symptomatic microcytic anemia and not due to an underlying primary psychiatric etiology. Anemia manifested in variable sensory experiences for the patient, including changes in the perception of smell, touch, and taste. The patient’s specific preference for books of a particular era could be influenced by changes in printing practices. Additionally, familial practices delayed recognition of xylophagia as an odd, learned behavior. Once recognized as untreated anemia and confirmed to have iron and zinc deficiency, oral supplementation was initiated throughout hospitalization with surgical surveillance following discharge.ConclusionThe presented patient developed a xylobezoar in the setting of severe symptomatic anemia precipitated by a combination of regular menses and a history of Roux-en-Y gastric bypass, leading to both monthly blood loss and chronic iron and zinc malabsorption, respectively. Although pica and xylophagia are frequently linked to primary psychiatric disorder or intellectual disability, and sometimes familial predisposition, the underlying trigger for these behaviors may, in some cases, stem from an unrecognized or untreated medical condition rather than a primary psychiatric disorder.